Endoscopic diverticulotomy of Zenker's diverticulum: management and complications - Mattinger, Cathrine; Hörmann, Karl (Dysphagia, 2002)
Background: Two approaches can be used for treating Zenker's diverticulum operatively: external or endoscopic. Methods: The records of 52 patients who underwent Zenker's diverticulum endoscopically were evaluated retrospectively. Twenty-two patients were treated with endoscopic scissors and 30 patients by carbon dioxide laser resection. The therapeutic concept of rigid endoscopic diverticulotomy was appraised with respect to the intraoperative and postoperative management for treatment and prevention of complications. Results: Forty-four of 52 patients were free of symptoms and 8 patients (15.4%) had a recurrence, 4 of which were within 4 months. Except for 2 cases, the recurrences could be reoperated endoscopically. The complication rate was 13.5% with hemorrhage the most common complication (3 cases). Two cases required an external approach to control severe bleeding. Conclusions: The endoscopic approach for Zenker's diverticulum is safe and effective if the surgeon is prepared to handle extraordinary complications, such as severe hemorrhage, quickly and sufficiently.
Elektronische Reproduktion der Druckausgabe
Gesehen am 06.05.2022